Towards a new standardized method for circulating miRNAs profiling in clinical studies: Interest of the exogenous normalization to improve miRNA signature accuracy. Issue 7 (2nd April 2016) - Vigneron, Nicolas; Meryet-Figuière, Matthieu; Guttin, Audrey; Issartel, Jean-Paul; Lambert, Bernard; Briand, Mélanie; Louis, Marie-Hélène; Vernon, Mégane; Lebailly, Pierre; Lecluse, Yannick; Joly, Florence; Krieger, Sophie; et al.
Abstract : Circulating miRNAs are promising biomarkers in oncology but have not yet been implemented in the clinic given the lack of concordance across studies. In order to increase the cross‐studies reliability, we attempted to reduce and to control the circulating miRNA expression variability between patients. First, to maximize profiling signals and to reduce miRNA expression variability, three isolation kits were compared and the NucleoSpin® kit provided higher miRNA concentrations than the other widely used kits. Second, to control inter‐sample variability during the profiling step, the exogenous miRNAs normalization method commonly used for RT‐qPCR validation step was adapted to microarray experiments. Importantly, exogenous miRNAs presented two‐fold lower inter‐sample variability than the widely used endogenous miR‐16‐5p reflecting that the latter is subject to both biological and technical variability. Although Caenorhabditis elegans miRNAs isolation yields were heterogeneous, they correlated to each other and to their geometrical mean across samples. The normalization based on the geometrical mean of three exogenous miRNAs increased the correlation up‐to 0.97 between the microarrays and individual RT‐qPCR steps of circulating miRNAs expression. Overall, this new strategy open new avenue to identify reliable circulating miRNA signatures for translation into clinical practice. Highlights: NucleoSpin kit offers the highest endogenous miRNA concentrations from serum/plasma. A common normalization based on exogenous miRNAs for discovery and validation steps. New strategy to increase both the signature accuracy and the overlap across studies.